The Study Effect of Lighting of Non – Regular on Statistical Properties for the Written Text on Whiteboard - Abtan, R. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
Lighting is a very important element of treatment if the color contains many imaging system (digital cameras) and the unit of light and the light within these units are not strong , but usefel when the light is low , in different lighting intensities conditions image quality will not persist good enough and image may become dark or slightly exposed to light which leads to lower the details in image where we can not modify contrast or light ness to compensate thr decrease without losing the light and dark deatials . So we went in this research to study the variation colored texts written on the painting and lighting cases of non –regular ( a few) and different distances . As the diversity of these texts written on the board at least the greater distance by increased distance and resolution less of text color for three bands color and lighting component .